Polyester crimped staple fiber comprising recycled polyester with excellent antibacterial properties, web obtained using the same, nonwoven fabric and spun yarn, methods for producing the same, and fiber processed products obtained using the same

JP2025035694AActive Publication Date: 2025-03-14TAKAGI CHEM

Patent Information

Application Number
JP2023142913
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14
Estimated Expiration
2043-09-04

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、主体繊維として、特定の銀系抗菌剤を用いた、機械捲縮を付与した再生ポリエステルを含む熱可塑性ポリエステル抗菌短繊維および機械捲縮を付与した熱可塑性ポリエステル非抗菌短繊維を、混綿用短繊維として用いることによって、布団綿として汎用的に用いられている潜在捲縮を付与した短繊維に比べ、カード性および収率に優れ、かつ抗菌性、圧縮率および回復率に優れたウェブ(綿)や、引き続く、針や接着剤、熱などを加えて繊維間の結合を強化することによって、抗菌性、着色性および難燃性に優れると共に、意匠性および機械的強度·伸度にも優れ、かつスケがなく、低目付で、軽量性に優れた不織布または紡績糸を提供できる。さらに、本発明に用いる銀系抗菌剤は、少量の添加によって抗菌性能を発揮できるため、異物として認識される繊維への負担が少なく、中空繊維、難燃繊維等、歩留および品質に難のある繊維の製造に適しており、かつ抗菌剤を樹脂に練り込んでいるため、耐久性、持続性等に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035694000015
    Figure 2025035694000015
  • Figure 2025035694000016
    Figure 2025035694000016
  • Figure 2025035694000017
    Figure 2025035694000017
Patent Text Reader

Abstract

To provide a nonwoven fabric obtained using a web comprising a silver-based antibacterial agent and recycled polyester, which has excellent antibacterial properties and fiber-blending cardability, exhibits minimal blending unevenness when blended with other non-antibacterial staple fibers, possesses superior antibacterial imparting ability, and excels in see-through resistance and mechanical strength.SOLUTION: A nonwoven fabric comprises a thermoplastic polyester including recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least partially composed of silver, is supported on an inorganic compound, the nonwoven fabric uses, as main fibers, antibacterial crimped staple fibers and non-antibacterial crimped staple fibers with an antibacterial activity value of 2.5 or higher and a fiber thickness of 1.0 to 10.0 dtex, the antibacterial crimped staple fibers account for 10 to 90 mass%, and the non-antibacterial crimped staple fibers account for 90 to 10 mass%, relative to 100 mass% of the total main fibers, the main fibers are blended and carded to form a web in which inter-fiber bonding is reinforced, the crimp of the main fibers is a two-dimensional mechanical crimp with a crimp count of 5 to 35 crimps / inch, a crimp ratio of 5 to 40%, and a residual crimp ratio of 3 to 35%, and the basis weight of the nonwoven fabric is 180 to 350 g / m2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polyester crimped staple fibers containing recycled polyester with excellent antibacterial properties and blended cotton carding properties, webs, nonwoven fabrics and spun yarns obtained using the same, their production methods, and textile processed products obtained using the same. More specifically, the present invention relates to antibacterial polyester crimped staple fibers containing environmentally friendly recycled polyester and a silver-based antibacterial agent as raw materials, and relates to a web that has little blending unevenness when the antibacterial crimped staple fibers are blended with other non-antibacterial crimped staple fibers, has excellent antibacterial property imparting ability, and is excellent in bulkiness and mechanical strength, and to a nonwoven fabric and spun yarn obtained using the web. [Background technology]

[0002] Sales of antibacterial processed products such as plastics and textiles began in Japan in the 1970s, and due to the outbreak of enterohemorrhagic Escherichia coli O-157 and severe acute respiratory syndrome SARS, they began to be distributed mainly in Asian countries. Recently, especially with the global spread of COVID-19, attention has been increasingly being paid to functional materials with antiviral and antibacterial properties.

[0003] Thermoplastic polyesters, especially polyethylene terephthalate (PET), are widely used as plastic molded products, sheets, synthetic fibers, etc., because of their excellent balance of mechanical properties, heat resistance, moldability, chemical resistance, etc., and because they are inexpensive. As SDGs and ESG investments have become global trends, recycled products, which were previously limited to certain fields, are now being actively used. Recycled polyester is a recycled material made from recycled PET made from PET bottles, PET scraps, PET scraps, etc., and other polyesters such as PBT and PEN. Recycled polyester fibers made from recycled PET have become widely used for automotive interior materials, cotton, clothing, interior goods fabrics, etc. However, compared to when virgin PET derived from petroleum is used as a raw material, the quality of the raw material is unstable, so the range of use is limited to cotton, nonwoven fabrics, and spun yarn made from short fibers.

[0004] Nonwoven fabrics, which are made of an assembly of fibers that forms a fabric-like material, are formed by combining a fleece-like cotton assembly, technically called a web, with a bonding process that physically and chemically bonds and entangles it. The main methods for forming fleece include the dry method, in which short fibers are carded using a carding machine and arranged in a fixed or random direction using an air flow called air laying, the wet method, in which short fibers are dispersed in water and combed into a net-like shape to form fleece, and the spunbond method, in which melted raw resin is directly dissolved and spun from the tip of a nozzle to form fleece from long continuous fibers. There are several methods for bonding fibers together, including the chemical bonding method, in which an emulsion adhesive resin is applied to the fleece by impregnation or spraying, and then heated and dried to bond the intersections of the fibers; the thermal bonding method, in which a fleece containing a low-melting point heat-sealing fiber is passed between heated rolls to bond the fibers together, or by applying hot air; and the needle punch method, in which the fleece is repeatedly pierced with a needle that moves up and down at high speed, and the fibers are entangled by the barbs engraved on the needle. The needle punch method is characterized by its high bulkiness and lack of separation between the fibers, and is used alone or in combination with other bonding methods. On the other hand, spun yarn is made through a spinning process in which short fibers are aligned in one direction and kneaded together.

[0005] On the other hand, as a method for antibacterializing fibers, Patent Document 1 discloses polyester staple fibers having a single yarn fineness of 2 to 8 denier, containing at least one silver-based antibacterial agent at 0.1 to 2.0 mass %, having a sterilization rate of less than 26% against Staphylococcus aureus, and showing a sterilization rate of 80% or more after carding. Patent Document 2 discloses antibacterial ball-shaped cotton containing 0.1 to 12.0 mass % of an inorganic antibacterial agent, having a single yarn fineness of 2 to 15 d (denier), a fiber length of 25 to 64 mm, and mechanically crimped polyester staple fibers intertwined to form balls with an average diameter of 3 to 20 mm. Patent Document 3 discloses antibacterial polyester fibers containing a heat-resistant discoloration inhibitor and a silver-based inorganic antibacterial agent, which do not discolor during or after the manufacturing process and have excellent antibacterial performance.

[0006] Patent Document 4 discloses an antibacterial polyester fiber containing an inorganic antibacterial agent carrying a silver component, with a silver component content of 30 to 200 ppm, a zinc content of 10 ppm or less, and a fiber-to-fiber dynamic friction coefficient of 0.20 to 0.35, which indicates the presence of optimal protrusions of the inorganic antibacterial agent on the fiber surface. Patent Document 5 discloses an antibacterial and antifungal polyester fiber obtained by an optimal combination of an inorganic antibacterial agent-containing master batch and an intrinsic viscosity of a polyester resin that is the main component of the fiber, in which the number of inorganic antibacterial agent particles present per unit cross-sectional area in the surface layer is 1.3 times or more the number of inorganic antibacterial agent particles present per unit cross-sectional area in the center, as determined by electron microscope observation of the cross section of the fiber. Patent Document 6 discloses an antibacterial and flame-retardant polyester fiber containing a phosphorus-based flame retardant and 0.01 to 10.0 mass% of an antibacterial agent, having a whiteness of 85.00 or more, and in which the polyester may be a recycled polyester. Furthermore, Patent Document 7 discloses a hollow crimped polyester having a crimp rate of 9 to 30 crimps / inch, a three-dimensional crimp (steric crimp) rate of 20 to 50%, and a crimp elasticity of 80% or more. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-237720 [Patent Document 2] JP 2000-34658 A [Patent Document 3] JP 2003-147637 A [Patent Document 4] JP 2009-108435 A [Patent Document 5] JP 2013-57163 A [Patent Document 6] JP 2015-140501 A [Patent Document 7] JP 2018-24957 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention relates to polyester crimped staple fibers containing a silver-based antibacterial agent and recycled polyester, which have excellent antibacterial properties and blended cotton carding properties, a web obtained using the same, and a nonwoven fabric and spun yarn obtained using the web, which relate to nonwoven fabrics and spun yarns that have little blending unevenness when blended with other non-antibacterial staple fibers, are excellent in antibacterial property imparting ability, and are also excellent in scalability and mechanical strength.

[0009] According to Patent Document 1, the antibacterial agent inside the fiber is exposed to the surface by performing the guarding treatment, and a good antibacterial rate is shown, according to Patent Document 2, it is said that a ball of cotton with sufficient antibacterial properties and excellent bulkiness can be obtained, according to Patent Document 4, it is said that by using a fiber having a specific range of fiber-fiber dynamic friction coefficient, it is possible to control the formation of protrusions on the surface of the inorganic antibacterial agent, and it is possible to impart high antibacterial performance and prevent discoloration over time, thread breakage and abnormal winding shape during production, and according to Patent Document 5, it is reported that if the difference in intrinsic viscosity between the inorganic antibacterial agent-containing master batch and the polyester resin that is the main component of the fiber is small, the antibacterial agent is not concentrated enough on the surface, and if the difference in intrinsic viscosity is large, fiber strength cannot be obtained. However, none of these cited documents mentions excellent mixed cotton carding properties, no mixed cotton unevenness, the effect of mixed cotton on antibacterial properties, or the inclusion of recycled polyester.

[0010] On the other hand, Patent Document 3 discloses that antibacterial polyester fibers can be mixed or composited with fibers that do not contain antibacterial agents, but does not mention the effect of the crimping method on antibacterial properties and unevenness in blending, or the inclusion of recycled polyester. Patent Document 6 describes that the polyester used may be recycled polyester, but does not mention blending of antibacterial fibers with non-antibacterial fibers or unevenness in blending. Patent Document 7 relates to hollow crimped polyester, and does not mention antibacterial properties.

[0011] For example, for textile products for automobile interiors, strict product standards and stable quality are required, and in addition to waste PET bottles and waste PET films, which are unstable in quality, recycled PET, such as PET blocks and scraps generated during manufacturing, which are unstable in quality, is widely used. Normally, rather than using a single fiber, it is common to blend multiple crimped staple fibers with different colors, physical properties, costs, etc. to satisfy the required characteristics. For this reason, the cardability of the crimped staple fibers obtained from recycled PET during blending is an important factor for commercialization. [Means for solving the problem]

[0012] In order to meet the needs for the development of functional materials with antiviral and antibacterial properties triggered by the global epidemic of infectious diseases, the present inventors have attempted to commercialize antibacterial fibers by producing antibacterial crimped staple fibers using recycled PET, which has unstable quality, instead of the conventional antibacterial fiber production that was mainly carried out using virgin PET derived from petroleum as a raw material, and have attempted to contribute to the SDGs and enhance ESG investment. As a result, it was found that even if recycled polyester, which has unstable quality, is used as a raw material, effective antibacterial performance can be obtained by adding a small amount of a specific antibacterial agent. However, only by using a specific antibacterial agent, it was not possible to obtain a sufficiently satisfactory mechanical strength such as yield, strength, and elongation. Therefore, as a result of extensive research into blending cotton with non-antibacterial staple fibers, it was found that antibacterial performance, carding properties and yield during carding, uniformity of nonwoven fabric, etc. are largely dependent on the shape and crimp performance of the staple fibers, and this led to the completion of the present invention. In addition, it was found that when an inorganic antibacterial agent containing a silver component supported on alkaline silica is used, it is easily transferred to the fiber surface by blooming during the drawing process, and high antibacterial performance can be exhibited even with a small amount added, and the effect can be enhanced by carrying out the same process under wet conditions, thereby strengthening the present invention. That is, the present invention provides the following (1) to (22).

[0013] (1) An antibacterial crimped staple fiber which is obtained by a melt-kneading spinning process, a drawing process, a crimping process and a cutting process of a resin raw material containing a thermoplastic polyester containing recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least a part of which is a silver component, is supported on an inorganic compound, and which has an antibacterial activity value of 2.5 or more, a fiber thickness of 1.0 to 10.0 decitex, and two-dimensional mechanical crimp, and which has a crimp number of 5 to 35 crimps / inch, a crimp rate of 5 to 40%, and a residual crimp rate of 3 to 35%, and which is excellent in blendability with non-antibacterial crimped staple fiber and carding properties; (2) The antibacterial crimped staple fiber according to (1), wherein the content of the silver component is 1 to 25 ppm by mass; (3) The antibacterial crimped staple fiber according to (1) or (2), which is a hollow fiber having a hollow ratio of 5 to 40%; (4) The antibacterial crimped staple fiber according to any one of (1) to (3), which is a flame-retardant fiber containing a phosphorus-based flame retardant and exhibits flame retardancy after three or more contacts with flame; (5) The antibacterial crimped staple fiber according to any one of (1) to (4), wherein the recycled polyester is 20 to 100% by mass and the virgin polyester is 80 to 0% by mass, relative to 100% by mass of the total amount of the thermoplastic polyester; (6) The antibacterial crimped staple fiber according to any one of (1) to (5), wherein the inorganic antibacterial agent contains a silver component supported on alkaline silica as an inorganic compound, and the concentration of the inorganic antibacterial agent is 0.05 to 0.85% by mass; (7) The antibacterial crimped staple fiber according to (6), wherein the drawing step is carried out in a state where the fiber surface is wet; (8) A web obtained by subjecting a resin raw material containing a thermoplastic polyester including recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least a part of which is a silver component, is supported on an inorganic compound through a melt-kneading spinning process, a drawing process, a crimping process and a cutting process, the web comprising antibacterial crimped staple fibers having a fiber thickness of 1.0 to 10.0 decitex and non-antibacterial crimped staple fibers, the antibacterial crimped staple fibers accounting for 10 to 90 mass% and the non-antibacterial crimped staple fibers accounting for 90 to 10 mass% relative to 100 mass% of the total amount of the main fibers, the main fibers being blended and carded, the crimp of the main fibers being two-dimensional mechanical crimp, the number of crimps of the mechanical crimp being 5 to 35 crimps / inch, the crimp percentage being 5 to 40%, and the residual crimp percentage being 3 to 35%, and the antibacterial activity value being 2.0 or more; (9) The web according to (8), wherein the content of the silver component is 0.5 to 15 ppm by mass; (10) The web according to (8) or (9), wherein the antibacterial crimped fiber is a hollow fiber having a hollow ratio of 5 to 40%; (11) The web according to any one of (8) to (10), wherein the antibacterial crimped staple fiber is a flame-retardant fiber that contains a phosphorus-based flame retardant and exhibits flame retardancy when exposed to flame three or more times; (12) The web according to any one of (8) to (11), wherein the recycled polyester is 20 to 100 mass% and the virgin polyester is 80 to 0 mass% relative to 100 mass% of the total amount of the thermoplastic polyester used in the main fiber; (13) A web according to any one of (8) to (12), wherein the inorganic antibacterial agent of the antibacterial crimped staple fibers is an inorganic antibacterial agent containing a silver component supported on alkaline silica as an inorganic compound, and the concentration of the inorganic antibacterial agent in the web is 0.05 to 0.085 mass%; (14) The web according to (13), wherein the stretching step is carried out in a state in which the fiber surfaces are wet; (15) The main fibers are antibacterial crimped staple fibers and non-antibacterial crimped staple fibers, which are obtained by melt-kneading spinning, drawing, crimping, and cutting processes of a resin raw material containing a thermoplastic polyester containing recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least a part of which is a silver component, is supported on an inorganic compound, and which have a fiber thickness of 1.0 to 10.0 decitex, and The antibacterial crimped staple fibers are 10 to 90% by mass, the non-antibacterial crimped staple fibers are 90 to 10% by mass, the main fibers are blended and carded to form a web that strengthens the bonds between the fibers, the main fibers are two-dimensionally mechanically crimped, the number of crimps of the mechanical crimp is 5 to 35 crimps / inch, the crimp rate is 5 to 40%, and the residual crimp rate is 3 to 35%, and the weight of the nonwoven fabric is 180 to 350 g / m 2 and further having an antibacterial activity value of 2.0 or more; (16) The nonwoven fabric according to (15), having a silver content of 0.5 to 15 ppm by mass; (17) The nonwoven fabric according to (15) or (16), wherein the antibacterial crimped staple fiber is a hollow fiber having a hollow ratio of 5 to 40%; (18) The nonwoven fabric according to any one of (15) to (17), wherein the antibacterial crimped staple fiber is a flame-retardant fiber that contains a phosphorus-based flame retardant and exhibits flame retardancy when exposed to flame three or more times; (19) The nonwoven fabric according to any one of (15) to (18), wherein the recycled polyester is 20 to 100 mass% and the virgin polyester is 80 to 0 mass% relative to 100 mass% of the total amount of the thermoplastic polyester used in the main fiber; (20) The nonwoven fabric according to any one of (15) to (19), wherein the inorganic antibacterial agent is an inorganic antibacterial agent containing a silver component supported on alkaline silica as an inorganic compound, and the concentration of the inorganic antibacterial agent in the nonwoven fabric is 0.05 to 0.085 mass%; (21) The nonwoven fabric according to (20), wherein the stretching step is carried out in a state in which the fiber surface is wet; (22) An antibacterial fiber product obtained by using the antibacterial crimped staple fiber according to any one of (1) to (7), the web according to any one of (8) to (14), or the nonwoven fabric according to any one of (15) to (21). Effect of the Invention

[0014] According to the present invention, by using thermoplastic polyester antibacterial staple fibers containing mechanically crimped recycled polyester and mechanically crimped thermoplastic polyester non-antibacterial staple fibers as staple fibers for blending cotton, it is possible to provide a web (cotton) that is excellent in carding property and yield, and has excellent antibacterial property, compression rate and recovery rate, compared with staple fibers with latent crimping that are generally used as bedding cotton, and a nonwoven fabric or spun yarn that is excellent in antibacterial property, colorability and flame retardancy, as well as in design, mechanical strength and elongation, has no voids, has a low basis weight and is lightweight, by subsequently strengthening the bonds between fibers by applying needles, adhesives, heat, etc. Furthermore, the silver-based antibacterial agent used in the present invention can exert its antibacterial properties by adding a small amount, so that it puts less strain on the fibers that are recognized as foreign matter, and is suitable for manufacturing fibers with poor yield and quality, such as hollow fibers and flame-retardant fibers, and also has excellent durability, sustainability, etc., because the antibacterial agent is kneaded into the resin. [Brief description of the drawings]

[0015] [Figure 1] This is a judgment sample used to evaluate the scalability of nonwoven fabric. [Diagram 2] 1 is a diagram showing a schematic shape of mechanically crimped staple fibers. [Diagram 3] 1 is a diagram showing a schematic shape of a latent crimped staple fiber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios.

[0017] The present invention relates to an antibacterial crimped staple fiber containing a thermoplastic polyester including recycled polyester and a specific inorganic antibacterial agent, which has an antibacterial activity value of 2.5 or more, a specific fiber thickness and a specific crimp function, and excellent blendability and carding properties with non-antibacterial crimped staple fibers, a web obtained from the antibacterial crimped staple fiber and excellent in antibacterial properties, compression ratio and recovery rate, and a nonwoven fabric or spun yarn obtained by strengthening the bonds between the fibers of the web, which has excellent antibacterial properties, designability, mechanical strength and elongation, is smooth, has a low basis weight and is lightweight, and an antibacterial fiber processed product obtained from these. In addition, an inorganic antibacterial agent containing a silver component supported on alkaline silica is easily transferred to the fiber surface by blooming during the stretching process, and can exhibit high antibacterial performance even with a small amount added, and the effect can be enhanced by carrying out the process under wet conditions. In this specification, unless otherwise noted, the numerical range indicated by "~" includes the upper and lower limits. For example, "10~30%" means "10% or more, 30% or less."

[0018] <Main fiber (thermoplastic polyester antibacterial crimped staple fiber and non-antibacterial crimped staple fiber)> The thermoplastic polyester antibacterial crimped staple fiber and the thermoplastic polyester non-antibacterial crimped staple fiber used as the main fiber in the present invention are obtained by a known method for producing thermoplastic polyester crimped staple fibers, which comprises subjecting a thermoplastic polyester resin to a melt-kneading spinning process together with an antibacterial agent and, if necessary, additives such as a colorant and a flame retardant, followed by a drawing process, a crimping process, a drying / heat setting process if necessary, and a cutting process. In this case, in order to impart lubricity to the fiber, a fiber oil can be used as an additive in each of the spinning, drawing, and crimping processes. There is no particular restriction on the thermoplastic polyester resin used in the present invention, and any polyester resin can be used as long as it is thermoplastic, regardless of its constituent components. The reason for limiting the use to thermoplastic polyester resins is that waste polyester can be reused if it is thermoplastic, and for example, it can be used as a fiber raw material as recycled PET (polyethylene terephthalate), etc., and these are in recent years because SDGs and ESG investment have become global trends and there is a greater demand for reuse than ever before. Recycled PET is widely used as an automobile interior material, but it is of inferior quality to petroleum-derived virgin PET, and because the raw material is unstable, it is not possible to obtain stable textile products from it, so it is not actually used much for manufacturing antibacterial textiles that contain antibacterial agents.

[0019] (Thermoplastic polyester resin) Polyester is a polycondensation product of polycarboxylic acid (dicarboxylic acid) and polyalcohol (diol). The polycarboxylic acid (dicarboxylic acid) component constituting such a thermoplastic polyester resin is not particularly limited, but examples thereof include terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, bis-(4-carboxyphenyl)sulfone, bis(4-carboxyphenyl)ether, 1,2-bis(4-carboxyphenyl)ethane, 5-sodium sulfoisophthalic acid, diphenyl-p,p'-dicarboxylic acid, p-phenylenediacetic acid, and trans-hexahydroterephthalic acid, as well as their alkyl esters, aryl esters, and ethylene glycol esters.

[0020] On the other hand, the polyalcohol (diol, glycol) component constituting the above-mentioned thermoplastic polyester resin is not particularly limited, but examples thereof include ethylene glycol, butylene glycol, 1,2-propylene glycol, 1,4-butanediol, trimethylene glycol, 1,6-hexanediol, 1,4-cyclohexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, bisphenol A, bisphenol S, and their ethylene glycol and polyethylene glycol adducts, diethylene glycol, and polyethylene glycol.

[0021] Furthermore, condensation type polyester resins of hydroxycarboxylic acids such as polylactic acids, and known flame retardant polyesters obtained by copolymerizing flame retardant components can be used. Depending on the combination of dicarboxylic acid components and diol components, the melting points of the resulting polymers (thermoplastic polyester resins and binder fibers) can be combined in a wide range of 150 to 300°C, and low melting point polymers can be used as binder fibers by combining them with high melting point polymers. Among these, polyethylene terephthalate (melting point 258°C), polybutylene terephthalate (melting point 243°C), and polyethylene naphthalate (265°C), which are used in large quantities and are inexpensively available, are particularly preferred as the thermoplastic polyester resin of the present invention. In addition, low melting point polymers include copolymerized polyesters consisting of polyethylene terephthalate segments with melting points of 180°C or less, polylactic acid resins, and the like. In addition to thermoplastic polyester fibers, polypropylene fibers, which are widely used, can be used as binder fibers. Thermoplastic polyester resins may be used alone or in combination. The binder fiber is used in an amount of 5 to 20 parts by mass per 100 parts by mass of the main fiber, but is not included in the main fiber of the present invention. The binder fiber is an optional component that is used appropriately as necessary.

[0022] The number average molecular weight of the thermoplastic polyester resin is not particularly limited, but is preferably 1,000 to 100,000, and more preferably 5,000 to 50,000. If it is 1,000 or more, thread formation is possible, and if it is 100,000 or less, the increase in viscosity is suppressed, making melt spinning easy. The number average molecular weight can be measured, for example, by gel permeation chromatography (GPC). Usually, the number average molecular weight can be substituted by the intrinsic viscosity, which is easy to measure, and the intrinsic viscosity is 0.05 to 2.53 dL / g, and preferably 0.19 to 1.40 dL / g. The intrinsic viscosity can be determined by a method in accordance with JIS K7390 (2003).

[0023] In addition, in the present invention, the thermoplastic polyester resin may be used after being discarded or scraps from the manufacture of industrial products. That is, the thermoplastic polyester resin of the present invention may include recycled polyester resin (particularly recycled polyethylene terephthalate (PET), recycled polybutylene terephthalate (PBT) and recycled polyethylene naphthalate (PEN) resins, with recycled polyethylene terephthalate resin being preferred). In the present invention, the discarded polyester resin broadly includes polyester resins other than products, such as used polyester resins and those that are not yet used but are out of spec and are not used as products. Examples of such discarded polyester resins include scraps and polyester resins below the standard grade from synthetic fiber manufacturers, film manufacturers, PET bottle manufacturers and polyester polymerization manufacturers, and polyester resins obtained by the Container and Packaging Recycling Law for General Waste. This allows for material recycling of waste materials that would otherwise be discarded or incinerated, which contributes to environmental conservation and is economically advantageous. Here, relative to 100% by mass of the total amount of thermoplastic polyester used in the antibacterial crimped staple fiber according to the present invention, or in the main fiber consisting of the antibacterial crimped staple fiber and non-antibacterial crimped staple fiber, it is preferable that the amount of recycled polyester is 20 to 100% by mass and the amount of virgin polyester is 80 to 0% by mass, it is more preferable that the amount of recycled polyester is 50 to 100% by mass and the amount of virgin polyester is 50 to 0% by mass, and it is even more preferable that the amount of recycled polyester is 80 to 100% by mass and the amount of virgin polyester is 20 to 0% by mass.

[0024] (Inorganic antibacterial agent) An inorganic antibacterial agent is an inorganic compound carrying an antibacterial metal such as silver, copper, or zinc, and among metals, silver has high antibacterial performance. The inorganic antibacterial agent used in the present invention is an inorganic antibacterial agent carrying an antibacterial metal component, at least a part of which is a silver component.

[0025] Examples of inorganic compounds that can support the silver component include inorganic adsorbents such as activated carbon, activated alumina, and silica gel, zeolite, hydroxyapatite, zirconium phosphate, titanium phosphate, potassium titanate, hydrous antimony oxide, hydrous bismuth oxide, hydrous zirconium oxide, hydrous titanium oxide, and inorganic ion exchangers.

[0026] The method for supporting the silver component on these inorganic compounds is not particularly limited, and examples thereof include a method of supporting the silver component by physical adsorption or chemical adsorption, a method of supporting the silver component by an ion exchange reaction, a method of supporting the silver component using a binder, a method of supporting the silver component by implanting a metal compound into the inorganic compound, and a method of supporting the silver component by forming a thin film of the metal compound on the surface of the inorganic compound by a thin film formation method such as vapor deposition, dissolution-precipitation reaction, or sputtering.

[0027] In particular, the silver-supported silica gel prepared by the ion exchange method is prepared by contacting the silica gel with a silver compound solution, maintaining a predetermined pH by adding an alkali, and bonding silver to the surface silanol groups of the silica gel. The pH range is preferably 4 to 10, more preferably 7 to 10. If the pH is lower than this, the amount of silver ion exchange is insufficient, and if it is higher than this, the degree of silica denaturation is high, which is not appropriate. Excess alkali can be easily removed by washing, filtration, calcination, etc. after preparation, but the silver-supported silica gel prepared in this way shows alkalinity when dispersed in water. Silica gel has a pH of about 5 in a water slurry, but in a silver nitrate solution, it releases hydrogen ions by ion exchange and has a pH of about 4. The silver-supported silica gel antibacterial agent according to the present invention has a pH of 6.5 to 9.0 in a water slurry obtained by dispersing 1 g of the antibacterial agent in 100 g of water. By carrying out ion exchange under an alkali, a large amount of silver components can be firmly captured by an inorganic compound, which enhances the antibacterial performance of the antibacterial agent, effectively expresses antibacterial properties with a small amount of addition, and is preferable because it can increase the persistence and durability. For example, there is a commercial product called NANOXCLEAN (registered trademark) NNXC-AA. Inorganic antibacterial agents containing silver components supported on alkaline silica are particularly preferred because they are easily transferred to the fiber surface by blooming during the drawing process and can exhibit high antibacterial performance even with a small amount added. In addition, the effect is enhanced by carrying out the process under wet conditions.

[0028] The average particle size of the inorganic antibacterial agent is preferably in the range of 0.1 to 10 μm. Here, the average particle size of the inorganic antibacterial agent means the cumulative 50% diameter (D50) corresponding to 50% of the cumulative distribution obtained from the cumulative distribution curve. If it is 0.1 μm or more, it is possible to prevent particle aggregation, and if it is 10 μm or less, it is possible to maintain thread breakage during production, winding stability, and further abrasion resistance.

[0029] The content of the silver component in the antibacterial crimped staple fiber according to the present invention is 0.5 to 100 ppm by mass, preferably 1 to 25 ppm by mass, and more preferably 1 to 15 ppm by mass. The concentration of the inorganic antibacterial agent carrying an antibacterial metal component, at least a part of which is a silver component, is 0.03 to 5% by mass, preferably 0.05 to 3% by mass, and more preferably 0.05 to 0.85% by mass. If the silver component content is 0.5 ppm by mass or more, antibacterial properties can be exhibited, and if it is 100 ppm by mass or less, discoloration over time can be suppressed. Note that "ppm by mass" means ppm (parts per million) by mass. In addition, if the concentration of the inorganic antibacterial agent is 0.03% by mass or more, antibacterial properties can be exhibited, and if it is 5% by mass or less, discoloration over time and thread breakage during fiber production can be prevented, winding of the spun yarn can be stabilized, and abrasion resistance can be maintained. In addition, the inorganic antibacterial agent of the present invention can be used as a master batch of 5 to 30% by mass. By making it into a master batch, the antibacterial agent can be uniformly dispersed in the fiber, and thread breakage during fiber production, winding stability, and abrasion resistance can be maintained. In order to be an antibacterial fiber, the antibacterial activity value against Staphylococcus aureus described in "JIS L 1902:2015 Antibacterial Test Method and Antibacterial Effect of Textile Products" of 2.0 or more is preferable, and considering blending with non-antibacterial fibers, 2.5 or more is preferable. More preferably, it is 2.5 to 6.0. If the antibacterial activity is 6.0 or less, antibacterial properties can be fully expressed, and adverse effects on production yield and other physical properties can be reduced.

[0030] Regarding the antibacterial action of silver-based antibacterial agents, both the active oxygen generated from the antibacterial agent in the presence of light and water and the silver ions eluted from the antibacterial agent react with microorganisms (bacteria) to damage the microorganisms and inhibit their proliferation. Viruses are smaller than bacteria, but they have DNA / RNA and require metabolism for activity, and many of the substances used as antibacterial agents can also be used as antiviral agents. Thus, the concentration of the antibacterial agent on the fiber surface is important for the expression of antibacterial properties, and the migration (blooming) of the antibacterial agent to the surface during the spinning process, drawing process, and drying / heat setting process is important, and the smaller the single fiber fineness, the more effectively the antibacterial action can be expressed in hollow fibers than in solid fibers. In addition, in hollow fibers, the antibacterial agent that has migrated to the inner surface of the hollow is less likely to fall off from the surface during the working process and use, and the antibacterial action can be sustained for a longer period.

[0031] (Other additives) The colorant used in the present invention may be any known organic or inorganic pigment. For example, organic pigments such as azo, anthraquinone, quinacridone, cyanine, cyanine green and cyanine blue, dioxazine, phthalocyanine, perinone, perylene, and polyazo; titanium yellow, ultramarine, iron oxide, red oxide, zinc oxide, titanium oxide, anatase titanium oxide, and rutile titanium oxide; and carbon-based inorganic pigments such as carbon black, graphite, spirit black, channel black, and furnace black may be used, but are not limited thereto. Usually, a desired coloring can be applied to the fiber by selecting a plurality of suitable pigments from among these colorants and mixing them in appropriate amounts. In addition, the colorant can be directly mixed with the raw material as an auxiliary material and spun to form a dyed fiber, thereby imparting light resistance (color deterioration prevention effect) to the fiber.

[0032] In addition to the coloring agent, other additives may be added to the extent that the spinnability and fiber properties are not impaired. Other additives include inorganic phosphorus-based flame retardants such as red phosphorus and ammonium polyphosphate, and phosphorus-based flame retardants such as melamine polyphosphate, polyphosphate esters, organic phosphorus metal salts, and phosphazenes, flame retardant assistants such as antimony oxide and biscumyl, flame retardants such as aluminum oxide, magnesium hydroxide, sodium carbonate, calcium carbonate, and talc, plasticizers such as phthalates, phosphate esters, and aliphatic carboxylic acids, stabilizers such as inorganic salts and metal soaps, antioxidants such as alkylphenols and alkylene bisphenols, and ultraviolet absorbers such as salicylic acid esters, benzotriazole, and hydroxybenzophenone. The antibacterial crimped staple fiber according to the present invention preferably contains a phosphorus-based flame retardant, and more preferably is a flame-retardant fiber that exhibits flame retardancy of at least three times after contact with flame.

[0033] Regarding the amount of these other additives, based on the total mass of the thermoplastic polyester resin composition (hereinafter also referred to as raw material resin) which is the raw material of the thermoplastic polyester antibacterial crimped staple fiber or thermoplastic polyester non-antibacterial crimped staple fiber used as the main fiber, the content of the colorant is 0.01 to 5 mass%, preferably 0.1 to 2 mass%, and the content of the flame retardant is 0.1 to 12 mass%, preferably 1 to 5 mass%. If the colorant is 0.01 mass% or more, it is excellent in that it can relatively easily color the textile product in various colors, and if it is 5 mass% or less, it is excellent in that it does not cause deterioration of light resistance such as discoloration. In addition, if the content of the flame retardant is 0.1 mass% or more, it is excellent in that it can impart sufficient flame retardancy, and if it is 12 mass% or less, it is excellent in that it can improve the yield by preventing thread breakage during spinning. The amount of other additives can be included within a range that does not impair spinnability and fiber properties.

[0034] (Spinning, drawing, shrinking, drying, heat setting and cutting processes) The subject fiber of the present invention is produced by continuously or discontinuously carrying out a series of steps such as kneading the thermoplastic polyester resin as the main raw material with the antibacterial agent and additives added as necessary, melt spinning, drawing, crimping, and cutting into short fibers, and includes a drying and heat setting step after crimping or cutting. These steps can be carried out by a commonly used method.

[0035] For example, the raw resin melt-kneaded by a single-screw or twin-screw extruder is extruded from a nozzle, water is added or, if necessary, a spinning oil is added, and the yarn is wound up to obtain an undrawn yarn. The cross-sectional shape at this time is arbitrary, and may be any of round cross-sectional fibers, irregular cross-sectional fibers, hollow fibers, etc. The irregular cross-sectional shape here refers to a cross-sectional shape other than a round cross-sectional shape among solid (term used for hollow) fiber cross-sections. Various shapes can be used for the irregular cross-section of solid fibers and the hollow cross-section of hollow fibers depending on the intended use. In the case of hollow cross-sectional fibers, the hollow cross-section has a hollow ratio of 5 to 40%, preferably 10 to 30%. If the hollow ratio is 5% or more, it is preferable because it is easy to achieve the desired weight reduction of the fiber, and if it is 40% or less, it is preferable because the holes are less likely to be crushed or cracked, and the weight reduction, sound absorption, fiber strength, etc. are prevented from decreasing. The hole shape of the nozzle used for producing hollow fibers includes ring-shaped and 1C, 2C, 3C, 4C, 5C, etc., which correspond to the number of air intakes for outside air. In order to maintain the hollow ratio of the present invention without being crushed by crimping, 1C, 2C, 3C, and 4C are preferred. Here, the ring-shaped hole shape is a nozzle used for producing core-sheath composite fibers, in which the sheath is resin and the core is air, and 1C is a normal nozzle, the hole shape is C-shaped, and there is one air intake with a part of the ring-shaped hole fixed. 2C has two air intakes in the ring shape (two C-shaped ones face each other to form a ring), 3C has three air intakes, 4C has four, and 5C has five air intakes. The number of holes is the number of holes per nozzle multiplied by the number of nozzles, and the productivity in spinning, i.e., the length and amount of fiber per certain time, is determined by the discharge rate, the number of holes, and the winding speed. The number of holes in the nozzle is not particularly limited since it is determined by the scale of the production equipment, but from the viewpoints of productivity and quality abnormalities due to yarn breakage and fusion (occurrence of sticks), it is preferably 200 to 2000. In the case of hollow fibers, it is preferably 200 to 1500 because of quality abnormalities due to yarn breakage and fusion.

[0036] The melt spinning process can be performed by any known method, not limited to wet or dry, but preferably by dry spinning. From the viewpoints of productivity, prevention of yarn breakage, and quality abnormality due to fusion, the take-up speed (winding speed) is 300 to 1000 m / min, and from the viewpoints of nozzle hole clogging, yarn breakage spinning, and quality abnormality due to fusion, it is preferable to perform melt spinning under conditions of 200 to 300 ° C., and the conditions are appropriately changed according to the yarn formation state to perform melt spinning under optimal conditions. In the case of hollow fibers, it is performed within the same condition range, but it is determined by the multiplication of several conditions such as the type of raw materials used, such as resins, antibacterial agents, and other additives, the product specifications, the external manufacturing environment such as outside temperature and humidity, and the characteristics of the manufacturing equipment, so it is more preferable to grasp the optimal conditions by performing preliminary experiments in advance and perform melt spinning, and stricter management conditions are required than for the production of solid fibers. In addition, in the case of hollow fibers, cooling at the nozzle outlet is particularly important, and it is necessary to control it so that the optimal hollow shape is obtained. More preferably, the ambient temperature at the nozzle outlet is within the range of 20 to 50° C., and may be determined in advance by carrying out a preliminary experiment or the like in conjunction with other conditions.

[0037] Since the undrawn yarn has insufficient molecular orientation, a process is required in which the undrawn yarn is drawn at an appropriate temperature below the melting point to fully align the molecules in the fiber axis direction. The undrawn yarn may be drawn as is in a continuous process, or it may be drawn after being taken up in a can or wound on a bobbin and aging. The drawing process may be one stage or multiple stages of two or more. From the viewpoint of ensuring the optimal strength and elongation of the fiber, the draw ratio is preferably about 1.0 to 6.0. A draw ratio of 1.0 or more is excellent in that sufficient strength can be maintained, and a draw ratio of 6.0 or less is excellent in that sufficient elongation can be maintained. In the case of hollow fibers, from the viewpoint of ensuring the optimal strength, elongation, and hollowness of the fiber, the draw ratio is 2.0 to 5.0, and a draw ratio of 2.0 or more is preferable in that sufficient fiber strength can be maintained, and a draw ratio of 5.0 or less is preferable in that an optimal hollowness can be maintained. In addition, there is no problem even if a contact or non-contact type heat source is used in the drawing process. In order to make the drawing process smooth, a fiber oil can be added to the extent that it does not adversely affect the fiber material. In the process of orienting the molecules in the drawing process, additives that are foreign to the fiber, such as antibacterial agents and flame retardants, are expelled from the oriented part of the resin, causing a blooming phenomenon, in which additives such as antibacterial agents migrate to the surface, and the silver component of inorganic antibacterial agents containing silver components supported on alkaline silica is particularly likely to migrate, which is further promoted under wet conditions. For this reason, it is particularly preferable to perform the drawing process when the fiber surface is wet (for example, in a hot water bath). This state is fixed by crystallization of the resin in the heat treatment process (drying and heat setting process) described later.

[0038] In the crimping process, a known mechanical crimping method that produces planar, so-called two-dimensional crimping can be used, and by setting appropriate conditions, the shape can be maintained stably for a long period of time, and the carding properties of the blended cotton can be improved. For example, in a method using a press-in crimper, the appropriate number of crimps, crimp rate, and residual crimp rate can be given to the fibers by adjusting the nip pressure and stuffing pressure, or by applying steam. The stronger the crimp, the more stable the crimp can be achieved, and it is preferable to set the nip pressure to 0.05 to 0.85 MPa, particularly 0.10 to 0.55 MPa, and the stuffing pressure to 0.05 to 0.85 MPa, particularly 0.10 to 0.45 MPa. The number of crimps, the crimp rate and the residual crimp rate are determined by delicate adjustment of both, and when the nip pressure and stuffing pressure are 0.05 MPa or more, respectively, the number of crimps, the crimp rate and the residual crimp rate can be effectively prevented from decreasing significantly, and when they are 0.85 MPa or less, the number of crimps, the crimp rate and the residual crimp rate can be prevented from increasing. As a result, it is excellent in that it is possible to effectively prevent the variation in the product from increasing and to further stabilize the quality. Regarding the number of crimps, the crimp rate and the residual crimp rate, in order to improve the bonding treatment between fibers by carding, needle punching, etc., it is preferable to carry out the crimping under similar conditions for antibacterial and non-antibacterial fibers, or for solid fibers, flame-retardant fibers and hollow fibers.

[0039] The number of crimps of the main fiber obtained by the drying and heat setting process described below is 5 to 35 crimps / inch, preferably 10 to 25 crimps / inch; within this range, a nonwoven fabric or spun yarn with a good texture can be obtained without any problems with the bonding and entanglement of the fibers. If the number of crimps is less than 5 crimps / inch, the bonding and entanglement of the fibers is insufficient, and the web may come off during the lamination process after passing through the card. If the number of crimps exceeds 35 crimps / inch, neps are likely to occur, causing a decrease in surface quality.

[0040] The shrinkage rate of the main fiber obtained by the drying and heat setting process described later is 5 to 40%, preferably 10 to 30%, and the residual shrinkage rate is 3 to 35%, preferably 7 to 25%. If the values ​​are within these ranges, a nonwoven fabric or spun yarn that is compatible with carding process passability and surface quality can be obtained. If either the shrinkage rate is less than 5% or the residual shrinkage rate is less than 3%, the fibers are not bonded or entangled sufficiently, and the web may come off in the lamination process after carding. If the shrinkage rate exceeds 40% or the residual shrinkage rate exceeds 35%, the cohesive force between the short fibers becomes too strong, which makes it easy for neps to occur and causes a decrease in surface quality.

[0041] Usually, mechanical crimping (also called two-dimensional crimping or apparent crimping) is used in the production of recycled PET fibers. In the spinning process, if anisotropic cooling or a spinning method using two thermoplastic resins with different thermal shrinkage rates (conjugate spinning) is used, three-dimensional crimping (also called three-dimensional crimping or latent crimping) occurs, and a light web with a large specific volume suitable for bedding such as bedding cotton is obtained. The crimped staple fiber used in the present invention is a fiber with strong crimping obtained by mechanical crimping.

[0042] The thickness (single yarn fineness) of the main fiber obtained by the drying and heat setting process described later is determined from the discharge rate (g / min), take-up speed (winding speed) (m / min), the number of holes in the nozzle, and the draw ratio during spinning, and can be expressed in decitex (dtex), which is the number of grams per 10,000 m of fiber length. The fiber thickness is preferably 1.0 to 10.0 decitex. A thickness of 1.0 decitex or more can prevent yarn breakage during spinning, while a thickness of 10.0 decitex or less can prevent the main fiber from becoming excessively strong, improving the processability of the fiber. In the present invention, the larger the surface area of ​​the fiber, the better the antibacterial performance, so the fiber thickness is more preferably 1.0 to 7.0 decitex. The single yarn fineness is determined by the spinning conditions of the fiber, and the value of the single yarn fineness is determined by the value obtained by the method described in "(1) Single yarn fineness (dtex)" in "A. Measurement method of crimped staple fibers" in the Examples section described later. By measuring the fiber thickness with a microscope or the like, the equivalent value of the single yarn fineness can be calculated by the method described in "(2) Equivalent value of single yarn fineness and hollow ratio obtained from microscope observation" in "A. Measurement method of crimped staple fibers" in the Examples section.

[0043] The cut length (fiber length) of the main fiber obtained by the drying and heat setting step described below is preferably 5 to 200 mm, and more preferably 10 to 80 mm. If the cut length (fiber length) of the main fiber is 5 mm or more, the fibers are sufficiently entangled with each other, which is excellent in that continuous fibers can be easily discharged by operations such as carding, and if the cut length (fiber length) of the main fiber is 200 mm or less, the fibers are effectively prevented from being too entangled, which is excellent in that uniform carding can be achieved.

[0044] Next, the drying and heat setting process uses a heating furnace to remove moisture that adhered during stretching, and then ages the fiber at a temperature above the glass transition temperature and below the melting point of the resin, promoting the crystallization of the resin and increasing the fiber strength. The heat-set long fibers are finally cut into short fibers by a cutter and then wrapped and packaged. The cut length is described above. The cutting process may be performed after the drying and heat setting process, or after the stretching and shrinking process.

[0045] As the textile oil, synthetic lubricants such as fatty acid ester type and polyether type, nonionic surfactants such as PEG (polyethylene glycol) type, ester type and amide type, anionic surfactants such as sulfonate type, phosphate type and carboxylate type, amphoteric surfactants, nonionic surfactants, and the like, which are usually used as textile oils, can be used. The amount of oil adhering to the fiber may be within a range that does not impair the effects of the present invention and can effectively exhibit the characteristics and functions of the textile oil, and is preferably 0.01 to 1.0 mass%, more preferably 0.05 to 0.5 mass%, based on the fiber obtained by the drying and heat setting process. If the amount of oil adhering to the fiber is within the above range, it is preferable in terms of excellent carding properties and punching properties.

[0046] <Webs and nonwovens> The web and nonwoven fabric can be produced by known methods, and specific examples of each are shown below.

[0047] Web manufacturing (blending and carding) For example, the above-mentioned subject fibers, antibacterial thermoplastic polyester crimped staple fibers and non-antibacterial thermoplastic polyester crimped staple fibers (subject fibers) are blended in a predetermined ratio (blending process), carded with a carding machine (carding process), and the staple fibers are aligned in a certain direction to produce a web. That is, the web used in the nonwoven fabric of the present invention is obtained by blending and carding the subject fibers. During carding, the surface of the fibers is worn away, exposing the silver component present inside to the surface of the fibers, thereby enhancing the antibacterial performance.

[0048] Nonwoven fabric manufacturing Next, the web is laminated using a cross wrapper to achieve a predetermined basis weight. The web is then punched with a needle punch machine (needle punching process) to entangle the short fibers (more specifically, three-dimensionally intertwined and integrated) and strengthen the bonds between the fibers to obtain a nonwoven fabric. That is, the nonwoven fabric of the present invention is a (uniform) web obtained by blending and carding the main fibers, which is three-dimensionally intertwined and integrated by needle punching, thereby strengthening the bonds between the fibers. When the web contains binder fibers, it can be heat-treated at a temperature equal to or higher than the melting point of the binder fibers (polymer) and lower than the melting point of the main fibers to obtain a final product with a stable shape.

[0049] The proportion of the blended crimped staple fibers is 10% by mass to 90% by mass, preferably 20% by mass to 70% by mass, and 90% by mass to 10% by mass, more preferably 70% by mass to 20% by mass, of the total amount of the main fibers. If the proportion of the antibacterial crimped staple fibers is less than 10% by mass (more than 90% by mass of the non-antibacterial crimped staple fibers), it does not lead to antibacterial properties of the nonwoven fabric, and if the proportion exceeds 90% by mass (less than 10% by mass of the non-antibacterial crimped staple fibers), it leads to increased costs due to the antibacterial agent, reduced yields, and reduced mechanical properties, which is not preferable. In addition, if the proportions of the antibacterial crimped staple fibers and the non-antibacterial crimped staple fibers are within this range, it becomes possible to mix colors to suit the needs of customers by blending, and it is possible to reduce the number of product numbers of the dyed fibers and reduce costs through mass production.

[0050] The number of webs to be laminated is preferably 3 to 10 from the viewpoints of preventing scalding of the nonwoven fabric, weight reduction, strength, etc., and the basis weight of the nonwoven fabric is preferably 180 to 350 g / m 2 is preferable, and 200 to 350 g / m 2 More preferably, 200 to 300 g / m 2 More preferably, the weight of the nonwoven fabric is 180 g / m 2 If it is less than 350 g / m, the nonwoven fabric will have a large uneven weight distribution, which may cause voids and may deteriorate the surface quality. 2If the antibacterial fiber is used, it is not preferable since it does not lead to a reduction in the weight of the nonwoven fabric. The web and nonwoven fabric of the present invention can be produced by any known method.

[0051] <Textile processing products> The antibacterial fiber processed products according to the present invention include stuffing for bedding, sofas, cushions, automobile interior materials, etc. obtained from the above-mentioned web (cotton) of the present invention, as well as curtains, carpets, uniforms, socks, underwear, etc. obtained from nonwoven fabrics and spun yarns obtained from the web. EXAMPLES

[0052] The present invention will be specifically described below with reference to Reference Examples, Comparative Reference Examples, Examples and Comparative Examples. The methods for measuring the respective property values ​​are as follows.

[0053] A. Crimp Staple Fiber Measurement Method (1) Single yarn size (dtex) A unit of fiber thread thickness, measured in grams per 10,000m. It was calculated using the following formula from the discharge rate (g / min) during spinning, the take-up speed (take-up speed) (m / min), the number of holes in the nozzle, and the draw ratio. In the case of hollow fibers, the hollowness was taken into account in the calculation.

[0054]

number

[0055] (2) Single fiber fineness and hollow ratio obtained from microscopic observation The cross-sectional area of ​​a single yarn (μm 2 ) and hollow area (μm 2 ) and the density of the PET resin was found to be 1.38 g / cm 3 The single yarn fineness equivalent value was calculated from the arithmetic average of the 10 points using the following formula, and the hollow ratio was calculated from the ratio of the hollow area to the cross-sectional area of ​​the single yarn.

[0056]

number

[0057] (3) Cut length (fiber length) The short fiber samples obtained in the cutting process were sampled from two locations, and the length of the short fibers in their natural state (see Figures 2 and 3) was measured. The arithmetic mean value (mm) of the measured values ​​of 10 samples in total, five samples from each sampling location, was calculated.

[0058] (4) Strength and elongation Measurements were performed in accordance with JIS L 1013 (8.5.1) using a strength and elongation tester (Orientec Co., Ltd., model: STA-1150, 2N). A single yarn was taken from the short fiber and the sample was attached to the knob of the testing machine in a loosely stretched state. Measurements were performed with a grip distance of 20 mm, an initial load (5.88 mN x dtex x 0.1), and the elongation at that time was C (mm), at a tensile speed of 20 mm / min. The tensile strength and tensile elongation were calculated using the following formulas, where A (cN) is the strength at break and B (mm) is the elongation at break. The decitex used in formula (3) was calculated using formula (1).

[0059]

number

[0060] (5) Shrinkage test The crimp percentage, residual crimp percentage and crimp modulus were measured in accordance with JIS L 1015 (8.12) using short fiber bundles instead of single yarns as test pieces. A short fiber with a width of about 4 mm and a mass of about 0.1 g was taken and accurately weighed using a precision balance to prepare a test piece, which was then pulled at a speed of 10 mm / min using a universal testing machine (SHIMADZU Autograph, manufactured by Shimadzu Corporation, load cell 50 N) and calculated using the following formula.

[0061]

number

[0062] Here, A is the length (mm) when an initial load (a load of approximately 0.001 mN / dtex on the end at the dead weight level) is applied, B is the length (mm) when a load of 4.41 mN x decitex is applied, and C is the length (mm) when the load is removed, left for 1 minute, and then the initial load is applied.

[0063] The crimp number was measured in accordance with JIS L 1015 (8.12) using a short fiber bundle instead of a single yarn as a test piece. A short fiber with a width of about 4 mm and a mass of about 0.1 g was taken and accurately weighed using a precision balance to prepare a test piece, which was then pulled at a speed of 10 mm / min using a universal testing machine (SHIMADZU Autograph, manufactured by Shimadzu Corporation, load cell 50 N) to count the number of crimps (n) at the point where it had stretched to a certain extent, and the crimp number was calculated according to the following formula.

[0064]

number

[0065] Here, A is the length (mm) when an initial load (a load of approximately 0.001 mN / dtex on the end at the self-weight level) is applied.

[0066] (6) Dry heat shrinkage rate According to JIS L1015 (8.12, b), a total of 10 single yarns were pulled out from the staple fiber, one at a time, a clip was attached to one end, the other was fixed to a piece of cardboard with tape, and the cardboard was fixed to a wall, and the single yarn length (A mm) was measured with a vernier caliper. Next, after drying at 170°C for 10 minutes, the yarn length (B mm) was measured again and calculated as the arithmetic average of the 10 pieces using the following formula.

[0067]

number

[0068] (7) Oil content The short fibers were loosened with a hand card to form a cotton-like material, and dried at 170°C for 10 minutes. Next, 2.000 to 2.020 g of cotton was accurately weighed (A), packed into a test tube, and immersed in 10 ml of methanol for 45 seconds, and the methanol liquid was squeezed out into a pre-weighed cup (B). The methanol liquid was then evaporated on a hot plate, and the cup was weighed (C), and the arithmetic average of the five points was calculated using the following formula.

[0069]

number

[0070] (8) Antibacterial properties Antibacterial properties were measured according to JIS L 1902: Textile bacterial liquid absorption method. This method is also the test method for the certification standards of "antibacterial and deodorant processed textile products" and "bacteriostatic processed textile products" of the Japan Textile Evaluation Technology Council (SEK Mark), a general incorporated foundation. The sample is soaked in bacterial liquid and the change in the number of bacteria after a certain period of time is examined.

[0071] Specifically, 0.4 g of the test piece was placed in a vial, 0.2 ml of the test bacteria liquid was dropped, and the vial was then capped. The vial was then cultured at 37°C for 18 to 24 hours, and 20 ml of washout liquid was added to wash out the test bacteria from the test piece, and the number of live bacteria in the washout liquid was measured by pour plate culture method or luminescence measurement method. The antibacterial activity value was then calculated according to the following formula.

[0072]

number

[0073] Here, A is the control sample's viable cell count after incubation, B is the control sample's viable cell count immediately after inoculation, C is the test sample's viable cell count after incubation, and D is the test sample's viable cell count immediately after inoculation. Antibacterial activity values ​​of 2 or higher are judged to have antibacterial effects.

[0074] B. Web Measurement Method (1) Cotton blend The antibacterial crimped staple fibers and the non-antibacterial crimped staple fibers were opened using a carding machine, and the cotton blending condition was visually confirmed (more specifically, visually confirmed by comparing with a good and bad sample prepared based on experience), and the results are shown in Table 3 below, with a circle mark for a good case, a triangle mark for a slightly good case, and an x ​​mark for a bad case. Note that a person skilled in the art can judge the cotton blending condition by visual inspection alone. In addition, when retesting the present Example, the web obtained in Example 1 can be used as a good sample and the web obtained in Comparative Example 1 can be used as a bad sample instead of the present sample, for example, to judge the quality of other Examples and Comparative Examples. In addition, by adding webs obtained in other Examples and Comparative Examples to the good and bad samples, more accurate samples (large samples) can be obtained, and the results can be used to judge the quality of the cotton blending condition of webs made under conditions other than those of the Examples and Comparative Examples.

[0075] (2) Card-based When the web was taken out of the carding machine, the wrapping around the cylinder, the occurrence of scum and neps, and the state of connection of the web were visually evaluated on a five-point scale by comparing with a sample created based on experience. The five-point scale is shown in Table 3 below, with 5: very good, 4: somewhat good, 3: good, 2: bad, and 1: very bad. Note that a person skilled in the art can judge the five-point scale of wrapping around the cylinder, the occurrence of scum and neps, and the state of connection of the web by visual inspection alone. In addition, when the example is to be retested, instead of the sample, for example, the web obtained in Example 14 is used as a sample with a rating of 5 (very good). Similarly, the web obtained in Example 13 is used as a sample with a rating of 4 (somewhat good), the web obtained in Example 10 is used as a sample with a rating of 3 (good), the web obtained in Example 26 is used as a sample with a rating of 2 (bad), and the web obtained in Comparative Example 6 is used as a sample with a rating of 1 (very bad). In this way, the webs of other examples and comparative examples can be evaluated (judged) on a five-point scale. In addition, by adding webs obtained in other examples and comparative examples to the five-level sample, a more accurate sample (large-scale sample) can be obtained, and it can also be used to judge the five-level evaluation of the cardability of webs obtained under conditions other than those of the examples and comparative examples.

[0076] (3) Web Yield The amount of staple fiber input to the carding machine and the yield of the completed web were measured to determine the amount of cotton loss and web yield (%).

[0077] (4) Specific volume, compression rate, recovery rate The measurements of the specific volume, compression ratio and recovery ratio were performed in accordance with JIS L 1097 (5.2, 5.3 methods). The web was folded with a floor area of ​​20 cm x 20 cm, and a web test piece adjusted to about 40 g was prepared and accurately weighed (W). Next, an acrylic plate (20 cm x 20 cm, 267.2 g) was placed on the obtained test piece, and a 2 kg weight A was placed on it for 30 seconds, and then the weight A was removed and left to stand for 30 seconds. This operation was repeated three times, and after removing the weight A and leaving it for 30 seconds, the heights of the four corners were measured, the arithmetic mean value (h0) of the bulk height was obtained, and the specific volume was calculated according to the following formula. This test was performed on three test pieces, and the web specific volume was obtained as the arithmetic mean.

[0078]

number

[0079] Weight B, weighing 4 kg, was placed on the test piece whose bulk had been measured for 30 seconds, and the heights of the four corners were measured and their arithmetic mean value (h1) was calculated. Weight B was then removed, and the test piece was left for 3 minutes, after which the heights of the four corners were measured and their arithmetic mean value (h2) was calculated from the following formulas: Compression rate and recovery rate. This test was performed on three test pieces, and the results of compression rate and recovery rate were shown as arithmetic mean values.

[0080]

number

[0081] C. Measurement methods for nonwoven fabrics (1) Actual weight (weight) The edge of the nonwoven fabric was cut to 40cm x 40cm, and the actual basis weight was calculated from the area and weight.

[0082] (2) Thickness of nonwoven fabric (bulk) The nonwoven fabric was cut into test pieces measuring approximately 5 cm x 5 cm in length and width, and a pressure of 0.5 kPa was applied in accordance with JIS L 1913 (6.1.1.A method), after 10 seconds the thickness was measured and the arithmetic average of the 10 points was calculated as the thickness (mm) of the nonwoven fabric.

[0083] (3) Scale The area was surrounded by a cardboard box, a red spotlight was placed at the bottom, and the top was covered with a translucent acrylic plate. A nonwoven fabric measuring 40 cm x 40 cm was placed on top of that, and red light was shone through to evaluate its transparency. In Fig. 1, which shows in black and white the areas without scale are red, and the areas with scale have a reddish tinge that fades with the degree of scale, and the areas with a higher degree of scale are lighter (lighter yellow), if there is even a part marked with an × (the part marked with a solid line near the × in the figure; the part with a relatively high degree of scale and displayed whiter), the scale is evaluated as ×; if there is only a △ part (the part marked with a solid line near the △ in the figure; the part with a relatively low degree of scale and displayed slightly whiter), the scale is evaluated as △; if there is only an ○ part (the part marked with an ○ in the figure; the part with no scale or almost no scale and displayed relatively black (or gray)), the scale is evaluated as ○. The area with scale was cut into a size of 1 cm in length and width, and the part with the lowest transmittance of ○ was set to 0% transmittance, and the average transmittance within 1 cm in length and width was calculated by image analysis processing to provide a quantitative guide to the scale. Transparency ○: Transmittance between 0% and 30%; Transparency △: Transmittance between 30% and 60%; Transparency ×: Transmittance between 60% and 100%.

[0084] (4) Strength and elongation of nonwoven fabric The strength and elongation were measured using a universal testing machine (SHIMADZU Autograph, manufactured by Shimadzu Corporation) in accordance with JIS L 1913 (6.1.2A, 6.3 method). The nonwoven fabric was cut to a width of 40 mm and a length of approximately 200 mm in the longitudinal direction (needle punching direction) and transverse direction (perpendicular to the needle punching direction), respectively, to prepare five test pieces for each direction. The test pieces were then attached to the testing machine at an initial load (enough so that the test pieces do not sag when pulled by hand) so that they were 150±1 mm long. A load was then applied at a tensile speed of 100 mm / min until the test pieces broke, and the strength (N / mm 2 ) and elongation (%) were measured, and the strength and elongation of the nonwoven fabric were calculated as the arithmetic average of the five pieces.

[0085] (5) Antibacterial properties The antibacterial properties were measured in the same manner as for the crimped staple fibers, according to JIS L 1902: bacterial solution absorption method for fibers.

[0086] (6) Flame retardancy The flame retardancy of the crimped short fibers was measured by a 45° flame test: JIS L 1091 D method (flame contact test) in accordance with the flammability test method for textile products (Japanese Industrial Standards). The test specimen is 100 mm long and weighs 1 g. The test specimen is inserted into the center of the test specimen support coil and maintained at a 45° inclination. The burner flame (flame height 45 mm) contacts the bottom end of the test specimen in the test specimen support coil, and the test specimen is heated until it melts and the flame goes out. The remaining bottom end of the test specimen is then contacted with the flame again. This operation is repeated until the test specimen melts and burns up to a position 90 mm from the bottom end. The test result is the one with the fewest flame contacts out of five measurements. If the flame contacts three or more times, the test specimen is deemed to have flame retardancy.

[0087] [Examples 1 to 8, Comparative Examples 1 to 4 and Reference Example 1 (Production of Crimped Staple Fibers)] The main raw materials were polyethylene terephthalate (PET) manufactured by Mitsubishi Chemical Corporation, virgin PET (with a trade name of "NOVAPEX") (intrinsic viscosity 0.65), or recycled PET adjusted to an intrinsic viscosity of 0.65 from PET scraps, PET remnants, and waste PET bottles, and the materials were kneaded in an extruder with the silver-based antibacterial agent, pigment, and flame retardant shown in Table 1, melt-spun at 230 to 285°C under the spinning conditions shown in Table 1, stretched in a hot water bath at the stretch ratio shown in Table 1, and then mechanically crimped or latent crimped was imparted using a push-in crimper by adjusting the nip pressure and stuffing pressure, dried and heat-set, and then cut with a rotary cutter (cutting machine) to obtain crimped short fibers with the silver concentration in the fiber (calculated value), appearance, shape, and physical properties shown in Table 2. The shape and performance of each fiber were determined by the above-mentioned method.

[0088] [Table 1]

[0089] [Table 2]

[0090] As for raw PET, the recycled PET was used alone in Examples 1 to 5, 7, and 8 and Comparative Examples 1 to 4, an equal mass mixture of the recycled PET and the virgin PET was used in Example 6, and the virgin PET was used alone in Reference Example 1. Among the results shown in Table 2, Reference Example 1, which used virgin PET alone, showed excellent results in strength and elongation.

[0091] As for the antibacterial agent, in Examples 1 to 6 and 8, Comparative Example 1 and Reference Example 1, a silver-based antibacterial agent NNXC AA manufactured by NANOX Co., Ltd., in which the silver component is supported on silica (silver concentration 0.24% by mass determined by a fluorescent X-ray analyzer (SQX method) equipped with a standardless analysis function), was used, and in Example 7, a silver-based antibacterial agent Novalon AGT330 manufactured by Toagosei Co., Ltd., in which the silver component is supported on zirconium phosphate (silver concentration 2.7% by mass determined by a fluorescent X-ray analyzer (SQX method) equipped with a standardless analysis function), was used. In the antibacterial test, all the other agents were 2 or more except for Comparative Examples 2 to 4, and were judged to have antibacterial action. Among the antibacterial agents, the silver-based antibacterial agent NNXC AA manufactured by Nanox Co., Ltd., supported on silica, gave better results than the silver-based antibacterial agent Novalon AGT330 manufactured by Toagosei Co., Ltd., supported on zirconium phosphate, despite the smaller amount added.

[0092] No pigment was added in Examples 1 to 3 and 5 to 8, Comparative Examples 1, 2, and 4, and Reference Example 1. When recycled PET was used, the crimped short fibers were light brown, and when virgin PET was used, the crimped short fibers were cloudy and transparent. In Example 4 and Comparative Example 3, a carbon-based black pigment (used as a master batch: carbon-based black pigment content 30%) was used, and the crimped short fibers were black. In Example 8 and Comparative Example 4, an inorganic phosphorus-based flame retardant (used as a master batch: phosphorus concentration 20%) was used as the flame retardant, and as a result, a value of 3 or more was obtained in the 45° combustion test, indicating that the material was flame retardant.

[0093] Regarding the shape of the nozzle during spinning, a circular cross section was used in Examples 1 to 4 and 6 to 8, Comparative Examples 1 to 4, and Reference Example 1, and crimped solid staple fibers were obtained in those cases. In Example 5, a 1C-shaped nozzle was used, and crimped hollow staple fibers with a hollow ratio of 16% were obtained.

[0094] The oil used was a fiber oil for nonwoven fabrics (a mixture of PEG-type and ester-type nonionic surfactants and phosphate-type and carboxylate-type anionic surfactants). Note that the oil used in the present embodiment and the like may be replaced with a fiber oil for other nonwoven fabrics, as long as it is a fiber oil for nonwoven fabrics that is commonly used and does not affect the performance evaluation content of the web and nonwoven fabric described below.

[0095] The short fibers imparted with mechanical crimps and obtained by normal cooling in Examples 1 to 8, Comparative Examples 2 to 4, and Reference Example 1 exhibited a two-dimensional zigzag crimp shape as shown in FIG. 2, while the short fibers imparted with latent crimps and obtained by anisotropic cooling in Comparative Example 1 exhibited a three-dimensional steric crimp shape as shown in FIG. 3.

[0096] [Examples 9 to 24, Comparative Example 5, and Reference Examples 2 and 3 (Web Production)] The antibacterial crimped staple fibers obtained in Example 1 and the non-antibacterial crimped staple fibers obtained in Comparative Example 2 were mixed into a nonwoven fabric having a basis weight of 200 g / cm. 2 The necessary amount was measured and pre-spread (cotton blended) to obtain the blend ratio shown in Table 3, and then the input amount shown in Table 3 was determined, and the carding machine was used to card three times while changing the direction to produce a web. The cotton loss at this time was measured to determine the yield, and the blending condition and carding properties were observed. The specific volume, compression rate and recovery rate were also determined, and are shown in Table 3 as Examples 9 and 10.

[0097] Moreover, instead of the short fibers of Example 1, the short fibers of any of Examples 2 and 3 and Examples 5 to 8 were used to prepare webs in the same manner as in Example 9. The results are shown in Table 3 as Examples 11 to 15, 17, 18, 20, 22, 23 and 24.

[0098] Furthermore, webs were produced in the same manner as in Example 9, except that the short fibers of Example 2 or 4 were used instead of the short fibers of Example 1, and either no short fibers of Comparative Example 2 or short fibers of Comparative Example 3 or 4 were used instead of the short fibers of Comparative Example 2. The results are shown in Table 3 as Examples 16, 19 and 21.

[0099] On the other hand, webs were produced in the same manner as in Example 9, except that the short fibers of Example 1 were not used or that the short fibers of Comparative Example 1 were used instead of the short fibers of Example 1, and the results are shown in Table 3 as Reference Example 2 and Comparative Example 5. Furthermore, a web was produced in the same manner as in Example 9, except that the short fibers of Reference Example 1 were used instead of the short fibers of Example 1, and the results are shown in Table 3 as Reference Example 3.

[0100] [Table 3]

[0101] The results in Table 3 show that the webs obtained using the mechanically crimped antibacterial crimped staple fibers (Examples 9 to 24) are superior in carding properties, blending condition, and web yield to the web obtained using the antibacterial crimped staple fibers with latent crimping (Comparative Example 5). The web obtained using the antibacterial crimped staple fibers with latent crimping, which are often used as batting for bedding, (Comparative Example 5) had a high non-uniform volume, but a low recovery rate.

[0102] When an inorganic phosphorus compound was used as a flame retardant (Examples 21 and 24), the carding property, blending condition and web yield were inferior to those when no inorganic phosphorus compound was used. The web obtained using the antibacterial hollow crimped staple fiber (Example 20) showed almost the same performance as the web obtained using the antibacterial solid crimped staple fiber, except for the compressibility.

[0103] Even when the concentration of the antibacterial agent in the antibacterial crimped staple fiber (Examples 1 to 3) and the mixing ratio of the antibacterial crimped staple fiber to the non-antibacterial crimped staple fiber were changed (Comparison between Example 9, Example 10 and Reference Example 2, Comparison between Example 12, Example 15 and Example 16, and Comparison between Example 17 and Example 18), there was little effect on the physical properties. It was found that the cardability improved when the target basis weight of the nonwoven fabric was increased (Examples 11 to 14).

[0104] Furthermore, no significant difference was observed between the webs obtained using virgin PET (Example 22 and Reference Example 3) and the webs obtained using recycled PET, as was observed in the production of staple fibers. Example 16, which used only antibacterial staple fibers, had comparable performance to Reference Example 2 and Example 15, which used a 50 / 50 blend ratio. As for the antibacterial performance of the web, an antibacterial test was not performed because the test pieces were significantly bulkier than the staple fibers and nonwoven fabrics, but it is estimated that the antibacterial performance is comparable to that of nonwoven fabrics.

[0105] [Examples 25 to 40, Comparative Example 6, and Reference Examples 4 and 5 (Production of Nonwoven Fabric)] The web obtained in Table 3 was punched using a needle loom (model NL-380) under the conditions of a moving width of 380 mm, a stroke of 75 mm, a stroke rate of 190 strokes / min, a web pitch width of 4 mm, a number of needles of 750, a needle pitch of 12.5 mm horizontally, a pitch of 30 rows, a vertical pitch of 10.0 mm, and a pitch of 25 rows, to produce a nonwoven fabric. The antibacterial property, flame retardancy, scalability, actual basis weight, thickness, longitudinal / lateral strength, and longitudinal / lateral elongation of the nonwoven fabric were measured, and the results are shown in Table 4 as Examples 25 to 40, Comparative Example 6, and Reference Examples 4 and 5.

[0106] [Table 4]

[0107] The results in Table 4 show that the nonwoven fabrics obtained using antibacterial crimped staple fibers to which mechanical crimping has been applied (Examples 25 to 40) are superior in antibacterial properties, scalability, strength and elongation to the nonwoven fabric obtained using antibacterial crimped staple fibers to which latent crimping has been applied (Comparative Example 6), except for the strength of Example 40. Furthermore, the nonwoven fabrics obtained using antibacterial crimped staple fibers to which mechanical crimping has been applied have slightly lower elongation than the nonwoven fabrics obtained using non-antibacterial crimped staple fibers to which mechanical crimping has been applied (Comparison between Example 32 and Reference Example 4).

[0108] In addition, the nonwoven fabric obtained by blending the antibacterial crimped staple fiber with the non-antibacterial crimped staple fiber with the mechanical crimping had an effective basis weight of 200 g / cm. 2 At this level or higher, the scalability is improved, and it can be seen that as the actual basis weight increases, the strength and elongation increase (Examples 27 to 30).

[0109] The nonwoven fabric obtained by blending hollow antibacterial crimped staple fibers with solid non-antibacterial crimped staple fibers was superior in antibacterial properties and elongation compared to the case where solid antibacterial crimped staple fibers were used (comparison of Example 36 and Example 28). It was also found that the original dyed antibacterial crimped staple fiber nonwoven fabric (Example 35) and the flame-retardant antibacterial crimped staple fiber nonwoven fabrics (Examples 37 and 40), to which a pigment and a flame retardant were added during the blending and spinning, could be colored and flame-retardant, respectively, without significantly affecting other physical properties.

[0110] When virgin PET was used as the raw material instead of recycled PET, the strength and elongation were slightly better than those containing recycled PET (Comparison between Example 38 and Reference Example 5). In addition, as for the silver-based antibacterial agent, those supported by silica (Examples 25 to 38 and Example 40) showed better antibacterial performance than those supported by zirconium phosphate (Example 39).

Claims

1. An antibacterial crimped staple fiber which is excellent in blendability with non-antibacterial crimped staple fibers and carding properties, and which is obtained by a melt-kneading spinning process, a drawing process, a crimping process and a cutting process of a resin raw material which contains a thermoplastic polyester containing recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least a part of which is a silver component, is supported on an inorganic compound, and which has an antibacterial activity value of 2.5 or more, a fiber thickness of 1.0 to 10.0 decitex, and is two-dimensional mechanical crimp, the number of crimps of the mechanical crimp being 5 to 35 crimps / inch, a crimp rate of 5 to 40%, and a residual crimp rate of 3 to 35%.

2. The antibacterial crimped staple fiber according to claim 1, wherein the content of the silver component is 1 to 25 ppm by mass.

3. 2. The antibacterial crimped staple fiber according to claim 1, which is a hollow fiber having a hollow ratio of 5 to 40%.

4. 2. The antibacterial crimped staple fiber according to claim 1, which is a flame-retardant fiber containing a phosphorus-based flame retardant and exhibits flame retardancy when exposed to flame three or more times.

5. The antibacterial crimped staple fiber according to claim 1, wherein the recycled polyester is 20 to 100% by mass and the virgin polyester is 80 to 0% by mass relative to 100% by mass of the total amount of the thermoplastic polyester.

6. 2. The antibacterial crimped staple fiber according to claim 1, wherein the inorganic antibacterial agent contains a silver component supported on alkaline silica as an inorganic compound, and the concentration of the inorganic antibacterial agent is 0.05 to 0.85% by mass.

7. The antibacterial crimped staple fiber according to claim 6, wherein the drawing step is carried out in a state in which the fiber surface is wet.

8. A web obtained by subjecting a resin raw material containing a thermoplastic polyester including recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least a part of which is a silver component, is supported on an inorganic compound through a melt kneading spinning process, a drawing process, a crimping process, and a cutting process, the web having antibacterial crimped staple fibers and non-antibacterial crimped staple fibers each having a fiber thickness of 1.0 to 10.0 decitex, the antibacterial crimped staple fibers accounting for 10 to 90 mass% of the antibacterial crimped staple fibers and 90 to 10 mass% of the non-antibacterial crimped staple fibers relative to a total amount of 100 mass% of the main fibers, the main fibers being blended and carded, the crimp of the main fibers being a two-dimensional mechanical crimp, the number of crimps of the mechanical crimp being 5 to 35 crimps / inch, the crimp percentage being 5 to 40%, and the residual crimp percentage being 3 to 35%, and the web having an antibacterial activity value of 2.0 or more.

9. 9. The web according to claim 8, wherein the content of the silver component is 0.5 to 15 ppm by mass.

10. The web of claim 8, wherein the antimicrobial crimped fibers are hollow fibers having a hollow ratio of 5 to 40%.

11. The web according to claim 8, wherein the antibacterial crimped staple fibers are flame-retardant fibers that contain a phosphorus-based flame retardant and exhibit flame retardancy of 3 or more times of contact with flame.

12. The web according to claim 8, wherein the recycled polyester is 20 to 100 mass% and the virgin polyester is 80 to 0 mass% relative to 100 mass% of the total amount of the thermoplastic polyester used in the subject fiber.

13. The web according to claim 8, wherein the inorganic antibacterial agent of the antibacterial crimped staple fibers is an inorganic antibacterial agent containing a silver component supported on alkaline silica as an inorganic compound, and the concentration of the inorganic antibacterial agent in the web is 0.05 to 0.085 mass%.

14. 14. The web of claim 13, wherein the stretching step is performed with the fiber surfaces wet.

15. The main fibers are antibacterial crimped staple fibers and non-antibacterial crimped staple fibers, which are obtained by a melt-kneading spinning process, a drawing process, a crimping process, and a cutting process of a resin raw material containing a thermoplastic polyester containing recycled polyester and an inorganic antibacterial agent in which an antibacterial metal component, at least a part of which is a silver component, is supported on an inorganic compound, and which have a fiber thickness of 1.0 to 10.0 decitex, and The nonwoven fabric is made of 10 to 90% by mass of the antibacterial crimped staple fibers and 90 to 10% by mass of the non-antibacterial crimped staple fibers, and the subject fibers are blended and carded to form a web that strengthens the bonds between the fibers. The subject fibers are two-dimensionally mechanically crimped, and the number of crimps in the mechanical crimp is 5 to 35 crimps / inch, the crimp rate is 5 to 40%, and the residual crimp rate is 3 to 35%. The nonwoven fabric has a basis weight of 180 to 350 g / m 2 and further having an antibacterial activity value of 2.0 or more.

16. The nonwoven fabric according to claim 15, wherein the content of the silver component is 0.5 to 15 ppm by mass.

17. The nonwoven fabric according to claim 15, wherein the antibacterial crimped staple fibers are hollow fibers having a hollow ratio of 5 to 40%.

18. The nonwoven fabric according to claim 15, wherein the antibacterial crimped staple fiber is a flame-retardant fiber that contains a phosphorus-based flame retardant and exhibits flame retardancy when exposed to flame three or more times.

19. The nonwoven fabric according to claim 15, wherein the recycled polyester is 20 to 100 mass% and the virgin polyester is 80 to 0 mass% relative to 100 mass% of the total amount of the thermoplastic polyester used in the subject fiber.

20. The nonwoven fabric according to claim 15, wherein the inorganic antibacterial agent is an inorganic antibacterial agent containing a silver component supported on alkaline silica as an inorganic compound, and the concentration of the inorganic antibacterial agent in the nonwoven fabric is 0.05 to 0.085 mass%.

21. 21. The nonwoven fabric of claim 20, wherein the stretching step is carried out with the fiber surfaces wet.

22. An antibacterial fiber processed product obtained by using the antibacterial crimped staple fiber according to any one of claims 1 to 7, the web according to any one of claims 8 to 14, or the nonwoven fabric according to any one of claims 15 to 21.

Citation Information

Patent Citations

  • Pre-oriented polyester yarns and preparation method thereof and polyester fiber fabrics and preparation method thereof

    CN105887240A

  • Nonwoven cotton dressing for negative pressure drainage and preparation method thereof

    CN111607894A

  • Antibacterial master batch, polyester DTY (Draw Textured Yarn) using antibacterial master batch and production method of polyester DTY

    CN113913000A

  • Anti-bacterial polyester staple

    JP1998237720A

  • Antimicrobial ball-shaped fiber

    JP2000034658A

Cited By

  • Preparation method of antibacterial self-curling regenerated polyester fiber

    CN122105681A